Ingestion of Partial Denture after General Anesthesia Induction and Ventılation: A Rare Case Report. (29th May 2019) - Akelma, Hakan; Salik, Fikret; Başol, Ömer; Bilge, Hüseyin; Yıldırım, Akif; Özgün, Şule
Abstract : The swallowing of dentures during general anaesthesia is a significant problem for anesthesiologists. It is seen more often in patients with psychiatric disorders, mental retardation, alcoholism, or poor quality dentures. It has become an important issue for anesthesiologists preoperatively due to the increase in the proportion of dentures associated with prolongation of life. In elderly, the use of partial fixed prosthesis increases and the risk of swallowing dentures is increased. In this case report, it was presented that the denture was swallowed spontaneously before intubation while the patient was ventilated preoperatively.